Genome-wide association studies unveils the genetic basis of cell wall composition and saccharification of cassava pulp - Sunvittayakul, Pongsakorn; Wonnapinij, Passorn; Wannitikul, Pitchaporn; Phanthanong, Phongnapha; Changwitchukarn, Kanokpoo; Suttangkakul, Anongpat; Utthiya, Supanut; Phraemuang, Apimon; Kongsil, Pasajee; Prommarit, Kamonchat; Ceballos, Hernan; Gomez, Leonardo D.; et al. (Elsevier, 2025)
Cassava (Manihot esculenta Crantz) is a key crop for starch and biofuels production. This study focuses on the polysaccharide composition and saccharification efficiency in cassava pulp through genome-wide association studies (GWAS), targeting the improvement of root characteristics for industrial use. We analyzed 135 partially inbred lines population, performing monosaccharide composition and saccharification analyses to reveal substantial variability in storage root biomass. Among 33 traits examined, 128 significant SNPs were associated with 23 biomass traits, highlighting a complex genetic architecture. Saccharification potential varied from 39 to 95 nmol Glu mg−1 h−1, with high broad-sense heritability for saccharification and several monosaccharide traits, indicating a strong genetic control. Our findings revealed that cassava pulp comprises similar proportions of pectin, hemicellulose, and cellulose in all genotypes. Correlation analysis showed significant associations between cellulose content and saccharification, suggesting that enhancing these traits can improve bioconversion efficiency. Negative correlations with glucose and glucuronic acid in hemicellulose and pectin fractions imply these components may inhibit saccharification. We identified 118 candidate genes associated with 21 traits, with many involved in stress responses affecting cell wall composition. This study verified 12 key candidate genes through sequence and expression analysis, including MANES_07G081200, a YTH domain-containing protein associated with saccharification. Several stress-response genes, such as MANES_04G118600 and MANES_09G174600, were linked to monosaccharide traits, suggesting that adaptive stress pathways influence biomass characteristics. This study provides insights into the genetic determinants of cassava pulp's saccharification and polysaccharide composition, aiding breeding efforts to develop cassava varieties optimized for industrial applications.